The dawn of a new era in onco-cardiology: The Kumamoto Classification. (1st October 2016) - Sueta, Daisuke; Tabata, Noriaki; Akasaka, Tomonori; Yamashita, Takayoshi; Ikemoto, Tomokazu; Hokimoto, Seiji
Abstract: The term "onco-cardiology" has been used in reference to cardiotoxicity in the treatment of malignant disease. In actual clinical situations, however, cardiovascular disease (CVD) associated with malignant disease and the concurrence of atherosclerotic disease with malignant disease are commonly observed, complicating the course of treatment. Patients with malignant disease associated with coronary artery disease often die from the cardiovascular disease, so it is essential to classify these disease states. Additionally, the prevalence of these classifications makes it easy to manage patients with malignant disease and coronary artery disease. We divided the broad field of onco-cardiology into 4 classifications based on clinical scenarios (CSs): CS1 represents the so-called paraneoplastic syndrome. CS2 represents cardiotoxicity during treatment of malignant diseases. CS3 represents the concurrence of atherosclerotic disease with malignant disease, and CS4 represents cardiovascular disease with benign tumors. This classification facilitates the management of patients with malignant disease and coronary artery disease by promoting not only the primary but also the secondary prevention of CVD. Highlights: We often encounter cardiovascular diseases associated with malignant diseases. It is usual to face complications related to therapy for either disease process. We proposed a novel recommendation of classification in "onco-cardiology."